Potential of Basil Seed (Ocimum basilicum) Simplicia as a Feed Supplement on the Histomorphometry and Muscle Damage of African Catfish (Clarias gariepinus) Exposed to Polystyrene Microplastics - Iga Novianti; Nurul Suwartiningsih (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the potential of basil seed simplicia supplementation in feed to mitigate histomorphometric alterations and muscle damage in African catfish (Clarias gariepinus) exposed to polystyrene (PS) microplastics. The experiment employed a Completely Randomized Design (CRD) consisting of five treatments: C (0 mg/L PS microplastics + 0% basil seed simplicia), PC (0 mg/L PS microplastics + 2% basil seed simplicia), NC (100 mg/L PS microplastics + 0% basil seed simplicia), T1 (100 mg/L PS microplastics + 2% basil seed simplicia), and T2 (100 mg/L PS microplastics + 4% basil seed simplicia). A total of 125 catfish were exposed to microplastics for 15 days. The observed parameters included myofiber diameter, myofiber area, muscle degeneration, and necrosis. The results indicated that exposure to PS microplastics significantly decreased myofiber diameter and area while increasing the levels of muscle cell degeneration and necrosis (P < 0.05). Supplementation with 2% basil seed simplicia (T1) significantly improved myofiber diameter and area and reduced muscle degeneration and necrosis compared with the negative control (NC), whereas supplementation with 4% basil seed simplicia (T2) showed relatively lower effectiveness. These findings suggest that supplementation of 2% basil seed simplicia in feed has the potential to mitigate histomorphometric alterations and muscle tissue damage in catfish exposed to polystyrene microplastics.